(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article discusses the issues related to developing speech in children with hearing impairments within inclusive education settings. It analyzes the specific features of speech development and the influence of hearing impairments on the child’s socialization and learning process. The role of special pedagogical approaches, speech therapy sessions, and modern technologies in inclusive education is examined. Additionally, the collaboration among teachers, parents, and speech-language specialists is highlighted as an essential factor in speech development. The article aims to identify effective methods for working with children who have hearing impairments.